ANALISIS MAKNA KONOTATIF DALAM KUMPULAN PUISI KISAHKU KARYA MIEKE NURHAYATI - Fatou'osa Laia (FAGURU: Jurnal Ilmiah Mahasiswa Keguruan, 2026)
This research was motivated by the researcher's desire to identify the connotative meaning in the poetry collection "My Story" by Mieke Nurhayati. The aim of this research is to describe the positive and negative connotative meanings contained in the poetry collection "My Story" by Mieke Nurhayati. The approach used in this research is a qualitative research approach with a descriptive research type. The data source in this research is the poem "My Story" by Mieke Nurhayati. Based on the results of the analysis, data presentation, and research findings regarding the connotative meanings used in the poetry collection "My Story" by Mieke Nurhayati, of the 20 selected poems, a total of 54 positive connotative meanings were found, namely: The hope of an educator, totaling 1. Thank you, my teacher. , totaling 1. Reality of life, totaling 2. Hum of Flowers, totaling 5. Three stems of roses, totaling 2. Conscience Cycle, totaling 4. Divine Gifts, totaling 2. Anxiety, totaling 4. Identity, totaling 5. Your charm, totaling totaling 4. Will not change, totaling 2. My suffering, totaling 2. Breath of Your Love, totaling 4. Despair, totaling 2. My complaints, totaling 3. If, totaling 3. Chasing shadows, totaling 5. Desires in despair, totaling 3. Meanwhile, the negative connotative meaning consists of 2 poems and 2 quotations, namely: Illusory Memories, totaling 1 and Desires in Hope totaling 1. Suggestions that can be given by researchers, especially for Indonesian language and literature teachers, through the collection of poems "My Story" by Mieke Nurhayati, can be used as as literary learning material to improve students' abilities in analyzing and appreciating literary works